Life Quality: More than Just a Concept. - Hilda Robaina Becerra; Ana Teresa Fernández Vidal; Alicia del Rosario Ramírez Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
The concept of life quality is controversial and ambiguous; for many health professionals it is an issue that posses difficulties when being discussed because it deals with qualitative scales. Its measurement depends on several variables that must be referred and provided by the patient. The achievements of social policies applied in Cuba, allow guaranteeing the accomplishment with all the life quality rights recognized in the legal instruments of United Nations. The specialized consultation for family planning and reproductive risk in the Area III Polyclinic of Cienfuegos provided an opportunity to develop the assessment of life quality in women whose records accounted for preconception risk. A one year study was conducted. The performances of different scales of life quality in the patients studied were compared at the point of admission in the specialized services and one year after the intervention. This research showed that the overall life quality rate in patients who integrated the universe of the study during the first consultation was inferior to the one perceived a year after the intervention in the multidisciplinary consultation.